2022
DOI: 10.1158/1055-9965.epi-21-1425
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Triage Strategies for Hr-HPV–Positive Women; A Longitudinal Evaluation of Cytology, p16/K-67 Dual Stain Cytology, and HPV16/18 Genotyping

Abstract: Background: We evaluated the longitudinal performance of three options: HPV16/18 genotyping (HPV16/18), cytology (LBC) and p16/Ki-67 Dual Stain cytology (DS) for the triage of Hr-HPV positive (Hr-HPV+) women within the cervical screening programme in Scotland. Methods: Data were derived from a cohort of Hr-HPV+ women (n=385) who participated in PaVDaG (Papillomavirus Dumfries and Galloway) study. Performance of triage strategies for detecting high-grade disease was assessed at three years (in women <50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, the increased sensitivity of p16/Ki-67 dual staining was lower than that of cytology [55,64,69]. This reduced specificity may lead to more false-positive results, where the test indicates the absence of a potential lesion.…”
Section: Study Outcomes On Dual Staining Efficacymentioning
confidence: 93%
See 3 more Smart Citations
“…However, the increased sensitivity of p16/Ki-67 dual staining was lower than that of cytology [55,64,69]. This reduced specificity may lead to more false-positive results, where the test indicates the absence of a potential lesion.…”
Section: Study Outcomes On Dual Staining Efficacymentioning
confidence: 93%
“…Recent advancements in cervical cancer screening have increased the efficacy of the p16/Ki-67 dual-staining technique, particularly for triaging human papillomavirus (HPV)positive women [64,65]. A growing body of research indicates that this dual-staining method outperforms traditional cytology in several key aspects, notably sensitivity and negative predictive value (NPV), albeit with a trade-off in specificity [14,56].…”
Section: Study Outcomes On Dual Staining Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Their results demonstrated significantly higher sensitivity and specificity for the detection of CIN2 or worse in HPV-positive women, as compared with HPV 16/18 genotyping in combination with cytology triage, and higher sensitivity but lower specificity when compared to cytology alone [53]. Interestingly, a study evaluating the clinical performance of LBC, p16/Ki-67 dual staining, and HPV 16/18 genotyping as triage strategies in HPV-positive women, demonstrated that the triage modality with the highest sensitivity and lowest negative predictive value for the detection of ≥CIN2, was a twostep triage including HPV 16/18 genotyping followed by LBC of hr-HPV non-16/18 + women [54].…”
Section: Dual Staining With P16/ki-67mentioning
confidence: 99%